A Hierarchical Peer-to-Peer Energy Transaction Model Considering Prosumer's Renewable Energy Preference. Issue 4 (2019) - Park, Dae-Hyun; Park, Yong-Gi; Roh, Jae-Hyung; Lee, Kwang Y.; Park, Jong-Bae
Abstract: This paper presents a hierarchical peer-to-peer-energy transaction model (P2P-ETM) considering the renewable energy preference. The model divides the characteristics of energy into normal and green energy. Green energy was assumed to be more expensive than normal energy, and prosumers and consumers considered in this model assumed that they have a preference for this green energy. Prosumer and consumer can trade energy with each other and buy normal and green energy from the main-grid. Prosumer can also sell surplus energy to the main-grid. To solve the energy transaction problem, we present a hierarchical approach considering the energy transaction and prosumers' goal. the purpose of each prosumer such as energy purchase cost minimization or energy sales maximization for energy transaction is considered in the first step as the self-scheduling of prosumers. After prosumers' self-scheduling we derive the energy transaction price and energy trading capacity through social welfare maximization. The proposed methodology is tested and validated on a virtual network. Through a case study using mixed integer linear programming (MILP), this model has demonstrated a decrease in the total operation cost in accordance with energy trading.